Effects of powerchair football: contextual factors that impact participation - Vandenbergue, A.; Barfield, J. P.; Ahmaidi, S.; Williams, S.; Weissland, T. (Adapted Physical Activity Quarterly, 2024)
The aim of this study was to identify contextual factors that negatively affect activity and participation among powerchair football (PF) players. Thirty-seven semistructured interviews were conducted with PF players (Mage = 27.9 ± 8.2 years) in France (n = 18) and the United States (n = 19). Participants reported acute back and neck pain as the primary morbidities resulting from PF participation, with sustained atypical posture in the sport chair as the primary cause. Competition-related physical and mental stress were also identified as participation outcomes. Accompanying the many benefits of PF, participants recognized negative impacts of discomfort, physical fatigue, and mental fatigue. Interventions such as seating modifications, thermotherapy to combat pain, napping to combat acute physical stress, and mental preparation to manage state anxiety were all identified as prospective interventions.